2017
DOI: 10.1039/c7dt01697b
|View full text |Cite
|
Sign up to set email alerts
|

Fixation of atmospheric CO2 as novel carbonate–(water)2–carbonate cluster and entrapment of double sulfate within a linear tetrameric barrel of a neutral bis-urea scaffold

Abstract: A meta-phenylenediamine-based disubstituted bis-urea receptor L1 with electron-withdrawing 3-chloro and electron-donating 4-methylphenyl terminals has been established as a potential system to fix and efficiently capture atmospheric CO as air-stable entrapment of an unprecedented {CO-(HO)-CO} cluster (complex 1a) within its tetrameric long straight pillar-like assembly entirely sealed by n-TBA cations via formation of a barrel-type architecture. L1 and its isomeric 4-bromo-3-methyl disubstituted bis-urea recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 64 publications
2
25
0
Order By: Relevance
“…[31][32][33] In some cases, urea groups can even capture atmospheric CO 2 as carbonates/bicarbonate. [24] X-ray structures resolved from single crystals obtained by slow evaporation of H 2 O/acetone saturated solution of TPP-Ur porphyrin, revealed the presence of four acetone molecules bound to the four urea groups through NÀH···O=C hydrogen bonding interactions ( Figure S21), confirming the stabilization of the carbonyls by urea moieties.…”
Section: Angewandte Chemiementioning
confidence: 90%
See 1 more Smart Citation
“…[31][32][33] In some cases, urea groups can even capture atmospheric CO 2 as carbonates/bicarbonate. [24] X-ray structures resolved from single crystals obtained by slow evaporation of H 2 O/acetone saturated solution of TPP-Ur porphyrin, revealed the presence of four acetone molecules bound to the four urea groups through NÀH···O=C hydrogen bonding interactions ( Figure S21), confirming the stabilization of the carbonyls by urea moieties.…”
Section: Angewandte Chemiementioning
confidence: 90%
“…[23] Das et al have shown a crystallographic structure of a neutral urea scaffold that fixes atmospheric CO 2 as carbonate clusters held together by an extended H-bonding stabilization. [24] Neumann and coworkers have recently reported a thiourea tether placed on the second coordination sphere of a rhenium catalyst that improved the electrocatalytic activity in the absence of external proton source. [25] However, the presence of weak acids, such as water, inhibits the activity of the latter system which will be problematic when aligning with the sustainable goal of using water as a free source of electrons and protons.…”
mentioning
confidence: 99%
“…In 2017, Manna et al 39 also reported the meta -phenylene diamine-based, halomethyl substituted isomeric dipodal bisurea receptors 21 and 22 , which were found to bind dianionic carbonate and sulfate in a 4 : 2 (host/guest) mode (Figure 10). Subjecting a mixed DMF/DMSO solution of receptor 21 and excess n -tetrabutylammonium hydroxide (TBAOH) to slow evaporation resulted in the formation of colorless needle-like crystals.…”
Section: Acyclic Anion Receptorsmentioning
confidence: 99%
“…Our choice of introducing urea groups in the second coordination sphere of an iron‐porphyrin catalyst was motivated by their ability to bind oxygen atoms of carbonyl groups as well as carbonates . In some cases, urea groups can even capture atmospheric CO 2 as carbonates/bicarbonate . X‐ray structures resolved from single crystals obtained by slow evaporation of H 2 O/acetone saturated solution of TPP‐Ur porphyrin, revealed the presence of four acetone molecules bound to the four urea groups through N−H⋅⋅⋅O=C hydrogen bonding interactions (Figure S21), confirming the stabilization of the carbonyls by urea moieties.…”
Section: Methodsmentioning
confidence: 89%
“…Das et al. have shown a crystallographic structure of a neutral urea scaffold that fixes atmospheric CO 2 as carbonate clusters held together by an extended H‐bonding stabilization . Neumann and co‐workers have recently reported a thiourea tether placed on the second coordination sphere of a rhenium catalyst that improved the electrocatalytic activity in the absence of external proton source .…”
Section: Methodsmentioning
confidence: 99%